Pengaruh Auditor Switching, Audit Tenure, dan Ukuran KAP Terhadap Audit Delay (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor - William Abednego Rante; Sabam Simbolon (Komunitas Dosen Indonesia, 2022)
This study aims to obtain empirical evidence of the effect of Auditor Switching, Audit Tenure and Public Accounting Firm Size on Audit Delay in Manufacturing Companies in the Industrial Sub-Sector for the period 2017-2020 Listed on the IDX. The research object used is a manufacturing sub - industrial sector listed on the Indonesia Stock Exchange (IDX) in the 2017-2020 period . Descriptive research method in the form of quantitative using secondary data from the IDX. The data processing of this research used a tool in the form of SPSS version 24 by using descriptive statistical tests, classical assumption tests, and hypothesis testing. The results showed that auditor switching partially affected audit delay with results of 3.153 > 1.98498 and significant 0.000 < 0.05 . The audit period partially affected audit delay with results of 3.646 > 1.98498 and significant 0.002 < 0.05 . Public Accounting Firm size partially affect the audit delay with the result -2.288 > 1.98498 and significant 0.024 < 0.05 . auditor switching, audit tenure and the size of the Public Accounting Firm simultaneously have an effect on audit delay with the results of 8.059 > 2.70 and significant 0.000 < 0.05. Keywords: Auditor Switching, Tenure Audit, Public Accounting Firm Size, Audit Delay